TELANG FLOWER EXTRACT IN OBESE WHITE MALE WISTAR RAT MODEL DERMAPEN WOUND HEALING: HAIR GROWTH AND HISTOPATHOLOGICAL SKIN TISSUE CHARACTERISTICS - Fransisca, Silvia; Harmila, Riva Nita; Oentari, Widyaningsih (Universitas Pahlawan Tuanku Tambusai, 2024)
Hair and skin defend against environmental hazards. Antioxidants like flavonoids and peptides in Telang flowers can improve health and treat many diseases. Telang flower extract cream (Clitoria ternatea) was tested for its effects on hair development, dermapen scar healing, and histopathology in obese male Wistar strain white rats (Rattus norvegicus). The Pharmacology and Therapy Laboratory, Department of Medicine, University of North Sumatra, conducted a true experimental research study with a post-test-only control group design from October to December 2023. The samples were 24 Wistar rats in 4 groups. Telang flower extract was given to groups 1, 2, 3, and 4 at 2.5%, 5%, and 7% per kg per body weight. Research data was handled with SPSS 25.0 for Windows. Treatment group 3 received 7% Telang flower extract and had the most hair growth. Telang flower extract at 2.5%, 5%, and 7% concentrations improves wound healing and has dense collagen. Thus, Telang flowers accelerate wound healing and hair development in fat persons.